Study the Role of Anti-Mullerian Hormone in Polycystic Ovarian Syndrome and its Correlation with Thyroid Disorder - Taghreed H. Al-Sadoon (Journal of Global Pharma Technology, 2019)
Many biochemical changes were associated with PCOS, the search for new parameters that affect by PCOS and vice versa is still an interesting field of research. In the present study, the level of serum antimüllerian hormone (AMH) level was studied and compared with many descriptive (age, body mass effect (BMI), waist/hip ratio (WHR). Thyroid stimulation hormones anti -thyroid peroxidase auto antibodies ,anti-TPO and anti -thyroglobulin antibodies Tg is performed by means of immunoassay sandwich with a final fluorescent detection (ELIFA) anti-thyroglobin. One hundred and five PCOS women patients were participated in the study. Their age was (31.35±6.61) year. The samples were collected from PCOS was diagnosed by specialist gynecologist doctors. Hormonal analysis was performed by using ready kit in accordance with the manufacturer's instruction (Biomerieux SA Etoile-France)AMH were measured by ELISA TSH and auto antibodies were performed by minividas full automated system method with a final fluorescent detection (ELIFA).